SPEECH DELAY THERAPY FOR CHILDREN USING THE AAC METHOD - Purba, Natalina; Astuti, Mira Kusumo (PrimaryEdu : Journal of Primary Education, 2020)
The purpose of this study (1) The factors that cause speech delay in early childhood (2) The treatment given by Permata Diakonia and parents? (3) The impact of speech therapy performed by Permata Diakonia using the AAC (Augmentative Alternative Communication) method. Methods: This study used a case study method with one child data analysis used qualitative data analysis with Miles and Huberman methods. Results: Sensory therapy that was given every day since the child was diagnosed late speaking had a very significant impact on the child's environmental response. A good response to this environment is a sign that the child can be given speech therapy using the AAC method which is given twice a week. From this study, it can be concluded that speech therapy using the AAC method significantly improves children's speaking ability. It should be noted that the key to success in this therapy is not changing therapists. Implication: speech therapy using the AAC method has implications for new ideas that will give  new ideas to new approaches to enrich speech therapy.Keywords: speech delay, sensory integration therapy, and speech therapy, AAC